Circadian misalignment disturbs the skeletal muscle lipidome in healthy young men. Issue 6 (12th May 2021) - Harmsen, Jan‐Frieder; van Polanen, Nynke; van Weeghel, Michel; Wefers, Jakob; Hoeks, Joris; Vaz, Frédéric M.; Pras‐Raves, Mia L.; van Kampen, Antoine H. C.; Schaart, Gert; van Moorsel, Dirk; Hansen, Jan; Hesselink, Matthijs K. C.; et al.
Abstract: Circadian misalignment, as seen in shift work, is associated with an increased risk to develop type 2 diabetes. In an experimental setting, we recently showed that a rapid day–night shift for 3 consecutive nights leads to misalignment of the core molecular clock, induction of the PPAR pathway, and insulin resistance in skeletal muscle of young, healthy men. Here, we investigated if circadian misalignment affects the skeletal muscle lipidome and intramyocellular lipid droplet characteristics, explaining the misalignment‐induced insulin resistance. Fourteen healthy men underwent one aligned and one circadian misalignment period, both consisting of ~3.5 days. In the misaligned condition, day and night were rapidly shifted by 12 hours leading to opposite eating, sleep, and activity times compared with the aligned condition. For each condition, two muscle biopsies were taken from the m. vastus lateralis in the morning and evening and subjected to semi‐targeted lipidomics and confocal microscopy analysis. We found that only 2% of detected lipids were different between morning and evening in the aligned condition, whereas 12% displayed a morning–evening difference upon misalignment. Triacylglycerols, in particular species of a carbon length ≥55, were the most abundant lipid species changed upon misalignment. Cardiolipins were decreased upon misalignment, whereas phosphatidylcholines consistently followed the same morning–evening pattern, suggesting regulation by the circadian clock. Cholesteryl esters adjusted to the shifted behavior. Lipid droplet characteristics remained unaltered upon misalignment. Together, these findings show that simulated shift work disturbs the skeletal muscle lipidome, which may contribute to misalignment‐induced insulin resistance.